Contribuição de um modelo LUTI para o planejamento integrado em transportes e uso do solo na região metropolitana de Belo Horizonte - Leonardo Furquim Werneck (2015)
Transportation planning and the urban planning are commonly addressed as independent disciplines, from different methodologies and theoretical frameworks. This research assumes that, in fact, this distinction is not only undesirable, as inadequate, in that it may be the baseline of segregating and individualistic territorial configuration featuring large contemporary cities, particularly in Latin America. Integrated planning of land use and circulation and transportation systems took his first steps in the early years of the 1960s, with the first urban crises, and gained strength from the 1990s, with the aid of computational tools, such as GIS systems, and with the consolidation of a more consistent theoretical framework. Many were the integrated planning software - the so-called LUTI - developed in recent years around the world, and some of them have been applied in the context of Latin America. The latest LUTI families have been developing towards breakdown and microscopic analysis, which has contributed to the maintenance of an environment of mistrust about its practical application outside the research world, according to the recognized deficiency that modeling features in general, especially with regard to its prospective capacity. This research was aimed to critically analyze the use of a LUTI model (TRANUS software) in a planning environment, that is, evaluating its applicability in the context of studies and urban development plans. Thus, more than the analysis of the quantitative results of the modeling, developed for the Metropolitan Area of Belo Horizonte, in Brazil, the study sought applicability evidences in the development of sectoral public policies based on criteria such as consistency and responsiveness of results, diversity of the indicators and time required for assembly and calibration of the model. The results presented showed that LUTI tools can be very useful in territorial planning, representing effective opportunity for integration of multidisciplinary policies, an inherent issue in contemporary urban planning.